A non-planar 2D covalent organic framework derived from a Z-shaped building unit. Issue 73 (20th August 2021) - Shan, Zhen; Wu, Miaomiao; Gu, Zhangjie; Nishiyama, Yusuke; Zhang, Gen
Abstract : Herein, a novel non-planar 2D COF with a stair-stepped structure was constructed from a Z-shaped building block for the first time. Abstract : Herein, a novel non-planar 2D COF with a stair-stepped structure was constructed from a Z-shaped building block for the first time. Compared with its similar planar COF, the unique stair-stepped non-planar COF possesses larger surface area and stronger fluorescence, which was further applied for specific explosive detection through a fluorescence quenching mechanism. This work not only extends the traditional planar 2D COF structures to unique non-planar structures based on the bottom-up design principle, but also expands the potential applications of COF materials.